2016
DOI: 10.1016/j.pbi.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose and callose synthesis and organization in focus, what's new?

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 82 publications
(42 reference statements)
1
70
1
4
Order By: Relevance
“…However, the mislocalization of CSLD3, a membrane protein, in root hairs of scyl2b mutants showed that SCYL2B plays a role in the vesicle trafficking pathway that mediates the PM localization of CSLD3 at the root hair tip. Previously, it was reported that CSLD3 is localized at the Golgi, ER, and PM (Favery et al, 2001;Bernal et al, 2008;Zeng and Keegstra, 2008;Park et al, 2011), and it was suggested that cellulose synthases, CSLD3 homologs, may be trafficked to the plasma membrane via the Golgi and TGN (Schneider et al, 2016). Taken together, these findings suggest that SCYL2B may be involved in the Golgi/TGN-mediated exocytosis/secretion of vesicles containing CSLD3.…”
Section: Discussionmentioning
confidence: 70%
“…However, the mislocalization of CSLD3, a membrane protein, in root hairs of scyl2b mutants showed that SCYL2B plays a role in the vesicle trafficking pathway that mediates the PM localization of CSLD3 at the root hair tip. Previously, it was reported that CSLD3 is localized at the Golgi, ER, and PM (Favery et al, 2001;Bernal et al, 2008;Zeng and Keegstra, 2008;Park et al, 2011), and it was suggested that cellulose synthases, CSLD3 homologs, may be trafficked to the plasma membrane via the Golgi and TGN (Schneider et al, 2016). Taken together, these findings suggest that SCYL2B may be involved in the Golgi/TGN-mediated exocytosis/secretion of vesicles containing CSLD3.…”
Section: Discussionmentioning
confidence: 70%
“…Cell wall patterning has been attributed to MT-based guidance of CSCs (Oda and Fukuda, 2013;Schneider et al, 2016). While the guiding principles have been largely resolved for primary cell wall cellulose synthesis, the corresponding mechanisms for secondary wall deposition have remained ill defined.…”
Section: Discussionmentioning
confidence: 99%
“…These walls largely comprise polysaccharides, of which cellulose, an unbranched, linear b-1,4-linked glucan, forms a significant constituent. Cellulose is synthesized at the plasma membrane by large cellulose synthase (CesA) complexes (CSCs; Schneider et al, 2016). The CSCs are composed of a heterotrimeric configuration of 18 to 24 CesAs where CesA1,CesA3,CesA2,5,6, and 9) CesAs produce primary wall cellulose in Arabidopsis thaliana, and CesA4, CesA7, and CesA8 comprise the CSCs necessary to make secondary wall cellulose (Persson et al, 2007;Desprez et al, 2007;Taylor et al, 2003;Atanassov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulase 2 and polygalacturonase were also identified as DEGs involved in cell wall modification in dormant tea shoots in a previous study. Although the two glucan polymers cellulose and callose are synthesized at the plasma membrane by cellulose or callose synthase complexes, respectively, much cross-talk occurs between the two processes (Schneider et al, 2016). Additionally, cell wall modification can affect the structure of plasmodesmata, causing rapid change in intercellular communication in response to environmental signals (Knox and Benitez-Alfonso, 2014).…”
Section: Discussionmentioning
confidence: 99%